La valorisation des fonds photographiques, ou comment concilier le droit d’auteur et l’accès au patrimoine culturel - David Pouchard (In Situ)
Archives services which contemplate digitising photos and making them available are expected to obtain authorisations to exploit the works from the authors concerned. Where collections of photographs are concerned, this is often difficult and raises several thorny issues. The first difficulty lies in identifying, amongst all the pictures, the ones for which authorisations are necessary. In legal terms, in positive law, the protection of a photographic work is subordinated to the common law condition of ‘originality’. But the definition and appreciation of originality is extremely difficult where photography is concerned, a process that is largely a technical one for reproducing reality. The realm of photography presents a second specific difficulty, which is, quite simply, the sheer numbers of works potentially concerned by exploitation authorisations. One photographer might diffuse several thousands of pictures during a career, and the sector is one where amateur practices are prevalent. Acquiring the necessary authorisations to exploit the pictures is all the more difficult, particularly in the case of collections of old photos, when the contractual information about copyright is unclear, incomplete or entirely lacking. From this point of view, photographs are often ‘orphaned’ works in archive collections, their authors impossible to identify and locate. To conclude, and confronted with all these difficulties, the question arises of whether archive services can diffuse the photos in their collections in legal conditions that are satisfactory. The beginnings of a reply are perhaps to be seen in some of the measures recently adopted in France or at the level of the European Union.